A comparative evaluation of floor slip resistance test methods. (30th September 2015) - Choi, Soo-Kyung; Kudoh, Rumi; Koga, Junko; Mikami, Takamasa; Yokoyama, Yutaka; Takahashi, Hiroki; Ono, Hidenori
Highlights: Three test methods for floor slip resistance were compared with user perceptions. A scale of user perception of floor surface slipperiness was constructed. The JIS A 1454 test method best represents footwear and floor surface conditions. JIS A 1454 results match user perceptions better than EN 13893 and ASTM D 2047. Abstract: Floor slipperiness is among the most influential parameters affecting the life safety of users. However, slip resistance coefficients determined using some methods do not correspond well to the perception of slipperiness by real users. From a life safety standpoint, a suitable test method for the slip resistance of a floor surface reflects slipperiness as sensed by users. We compared the results of three slip resistance test methods and their correspondence with sensed slipperiness as reported by users. The JIS A 1454 test method was found to be a better test of slip resistance than EN 13893 and ASTM D 2047.